Productividad, Eficiencia y Arrendamiento Agrícola: un análisis mediante Fronteras Estocásticas - Franetovich, Esteban; Pace Guerrero, Ignacio Raul (Asociación Argentina de Economía Agraria, 2024)
The objetive of farmers is maximize profit. However, there is a disagreement in literature related to productivity and efficiency differences between producers that own land and those who rent land, due to potencial incentive problems. This paper makes an exploratory analysis of production data of a sample from Pampean Region counties to study differences in agricultural productivity by kind of land tennure. Stochastic Frontiers Analysis were used for each crop,following the example from Coelli et al.,(2005), with microdata of National Agricultural Census of 2018 and production data from Argentinian Agricultural Departament at county level. It was concluded that rent rate has no statistically significant effect on wheat but significant and negative effect on corn, soybean and sunflower. However, it was found that rent rate has no significance in a practical or economical sense.